Efektivitas Buku Ajar Berbasis Pendekatan Saintifik Pada Mata Kuliah Geometri dan Pengukuran - Siti Hawa; Toybah; Vina Amilia Suganda (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2021)
The purpose of this study was to determine the level of effectiveness of textbooks based on a scientific approach in the Geometric and Measurement courses in the PGSD FKIP Sriwijaya University Study Program. The approach used is development research with descriptive quantitative methods. The data collection technique is a test. The test is used to collect data from research subjects, namely students in semester 3 (three) to determine the level of effectiveness of this textbook, namely giving tests before and after being given material in the textbook that has been developed. The results showed that based on the acquisition of pretest and posttest values, it was known that there was an increase of 48% with an N-Gain of 0.68. So it can be concluded that this textbook has effectiveness in order to help students better understand the material being studied in the moderate category.